2013
DOI: 10.1039/c3ta12790g
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic magnetic iron oxide spheres for high performance Li-ion battery anode: a new pulsed laser induced reactive micro-bubble synthesis process

Abstract: Spherical particles of iron oxide (mainly Fe 3 O 4 with a small contribution of a-Fe 2 O 3 ) having a size of about $200 nm are synthesized from bulk commercial a-Fe 2 O 3 powder by a pulsed excimer laser irradiation technique in solution phase. The dispersed a-Fe 2 O 3 powder is subjected to a pulsed excimer laser (248 nm) irradiation at an energy density of $214 mJ cm À2 and pulse repetition rate of 10 Hz for 5 h under constant stirring in the presence of aqueous ammonia. It has been observed that the a-Fe 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…[ 352 ] Ji et al [ 353 ] fi rst demonstrated the performance of the Fe 3 O 4 -graphene composite as a conversion anode with layered type LiNi 1/3 Mn 1/3 Co 1/3 O 2 as the cathode. The magnetite phase is a perfect example of the inverse spinel structure with cubic close packed array of ions, where half of the octahedral sites are fi lled by all the Fe 2+ ions and Fe 3+ ions occupy the remaining octahedral and tetrahedral sites.…”
Section: Fe 3 Omentioning
confidence: 99%
“…[ 352 ] Ji et al [ 353 ] fi rst demonstrated the performance of the Fe 3 O 4 -graphene composite as a conversion anode with layered type LiNi 1/3 Mn 1/3 Co 1/3 O 2 as the cathode. The magnetite phase is a perfect example of the inverse spinel structure with cubic close packed array of ions, where half of the octahedral sites are fi lled by all the Fe 2+ ions and Fe 3+ ions occupy the remaining octahedral and tetrahedral sites.…”
Section: Fe 3 Omentioning
confidence: 99%
“…The observed Raman results are consistent with the HR‐TEM and XRD studies, indicating the formation of inverse spinel magnetite particulates over rGO nanosheets. Furthermore, the A 1g vibration mode of the Fe 3 O 4 peak appeared at 668 cm −1 , which agrees well with the literature value for the formation of Fe 3 O 4 in the composite . To estimate the rGO content of the Fe 3 O 4 ‐rGO material, quantitative thermogravimetric analyses were performed by heating the samples at a rate of 10 °C min −1 in air (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…These electrodes are anticipated to improve the energy density and certainly boost the high power density as well. Among these metal oxides, magnetite (Fe 3 O 4 ) has been gained great attention as conversion type anode because of the advantages like high theoretical capacity (924 mAh g −1 ), low cost, eco‐friendly and naturally abundant ,, . Nevertheless, to the best of our knowledge, the magnetite phase has not been paired with Fe‐based cathode (i. e. LiFePO 4 ) for the fabrication of high energy LIB ,.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical reversible capacity is high (928 mAh g À1 ), it is abundant as it occurs in nature as the mineral magnetite, it is nontoxic; its low cost and high corrosion resistance are other characteristics. The limits come, as usual with all the anode elements based on conversion reactions, the degradation of the battery coming from the large change of volume (200 % [593]. An intermediate situation is provided by recent experiments on clusters of mesoporous 11-12 nm sized nanoparticles, with carbon-coating through bottom-up self assembly approach [594].…”
Section: Fe 3 Omentioning
confidence: 98%